Technical Evaluation and Financial Analysis of a Retrofitting Investment Project for Production Machinery in a Cement Plant - Taufik; Nilda Tri Putri; Muhammad Kevin (Jurnal Optimasi Sistem Industri, 2023)
In today's rapidly evolving industrial landscape, businesses are increasingly challenged to strike a balance between enhancing productivity and maintaining product quality. Company X, a renowned cement manufacturer in Indonesia, relies heavily on four key raw materials, among which clay is particularly crucial for the raw mix. Recent trends have shown a decrease in the Al2O3 composition of clay, necessitating adjustments in clay capacity to uphold quality standards. A thorough technical evaluation of the plant highlighted that a significant number of critical machines, totaling 17, were operating with mechanical availability below the desired threshold. Additionally, a utility analysis pinpointed a shortfall in meeting the required clay tonnage, leading to the identification of machines that would benefit from retrofitting. The financial implications of this initiative were substantial, with the initial investment for the upgrades and subsequent operational costs in the first year being considerable. Yet, this expenditure was offset by a notable profit in the first year post-retrofitting. Key financial metrics further underscored the project's viability: a highly favorable Net Present Value (NPV), an impressive Internal Rate of Return (IRR), a rapid Payback Period (PP), and a significant Profitability Index (PI). These parameters, derived from an exhaustive analysis, clearly support the strategic decision to invest in retrofitting the production machinery at Company X's cement plant, illustrating the project's feasibility and the prospective benefits of this investment.